Investigation of electrospinning process of fluoropolymers and properties of electrospun microfiberous materials - V. A. Kozlov; Y. N. Filatov; Y. A. Naumova (Тонкие химические технологии)
To substitute the foreign filtering membrane Millipore FSLW, which currently in use on some of Russian and Ukrainian NPP the nonwoven fibrous material, obtained by means of electrospinning from spinning solutions of mixtured fluoropolymers F-42 and SKF-26, have been produced. The influence of polymer ratio on fibrous material properties was investigated.